Peningkatan Pemahaman Konsep IPA dengan Menggunakan Model Inkuiri di Sekolah Dasar - Amanda, Nadilla Resti; Surya, Yenni Fitra; Hardi, Vitri Angraini; Pebriana, Putri Hana; Fadhilaturhami, Fadhilaturhami (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This research was conducted due to low achievements on students' understanding in science concepts at Class V, SDN 003 Bangkinang. One of the solutions to overcome this problem is to implement an inquiry learning model. This research aims to describe the improvement of students' conceptual understanding on seeing because of light, hearing because of sound topic by implementing the inquiry model at class V students of SDN 003 Bangkinang. This is a Classroom Action Research (CAR) which was carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation and reflection. The research was conducted in July, 2023. The subjects of this study were grade V students totaling 32 people, with the number of female students were 15 people, and male students were 17 people. The data collection techniques employed in this research were observation, documentation, and tests. The findings in cycle I shows that the students' understanding were classified as sufficient with average score is 68.,94; out of 32 students only 19 students were complete, namely 59,38%. In cycle II it was classified as good with an average of 80.24; out of 32 students there were 29 students who were complete, namely 90.63%. Based on its findings, it can be concluded that implementing Inquiry learning model can improve students' understanding of science concepts on the material of seeing because of light, hearing because of sound in Class V students of SDN 003 Bangkinang.